2002
DOI: 10.1897/1551-5028(2002)021<1753:loctep>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

LOSS OF CAPACITY TO ELEVATE PLASMA CORTISOL IN RAINBOW TROUT (ONCORHYNCHUS MYKISS) TREATED WITH A SINGLE INJECTION OF o,p′-DICHLORODIPHENYLDICHLOROETHANE

Abstract: The organochlorine o,p'- dichlorodiphenyldichloroethane (o,p'-DDD) is a metabolite of dichlorodiphenyltrichloroethane (DDT), known for its adrenolytic actions in birds and mammals. The effects of o,p'-DDD on the cortisol stress response were investigated in rainbow trout, Oncorhynchus mykiss, in a dose-response study in vivo. A dose-dependent decrease in plasma cortisol levels was observed on days 7 and 14 after a single i.p. injection of o,p'-DDD. Treatment with o,p'-DDD had no effect on weight gain, hematocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…DDT: Benguira et al, 2002), and metals (Gagnon et al, 2006;Gravel et al, 2005;Hontela, 1998;Laflamme et al, 2000;Norris et al, 1999). In particular, effects on the stress axis similar to those observed in the present study have recently been reported for rainbow trout, Oncorhynchus mykiss, exposed to municipal waste water effluent for 14 days (Ings et al, 2011a,b).…”
Section: Consistency Of These Findings With Previous Studiessupporting
confidence: 88%
“…DDT: Benguira et al, 2002), and metals (Gagnon et al, 2006;Gravel et al, 2005;Hontela, 1998;Laflamme et al, 2000;Norris et al, 1999). In particular, effects on the stress axis similar to those observed in the present study have recently been reported for rainbow trout, Oncorhynchus mykiss, exposed to municipal waste water effluent for 14 days (Ings et al, 2011a,b).…”
Section: Consistency Of These Findings With Previous Studiessupporting
confidence: 88%
“…Thus, a temporary loss of osmotic control in fish larvae may increase their susceptibility to predation or impair their feeding abilities (Sclafani et al, 1997). Disruption of normal cortisol secretion in early life stages may also affect their survival by reducing the ability to cope with acute stressful situations and by inducing adverse secondary effects on osmoregulation, growth, development and immune function (Benguira et al, 2002;Gravel et al, 2005;Kennedy and Farrell, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Blood glucose level increases on application of various stressors like chemical dichlorodiphenyldichloroethane (Benguira, Leblond, Weber & Hontela 2002) in rainbow trout and high aluminum concentrations (Ytrestøyl, Finstad & Mckinley 2001) in Atlantic salmon ( Salmo salar ). In our findings, the blood glucose level was significantly ( P <0.05) influenced by the addition of dietary pyridoxine in the diet of L. rohita fingerlings.…”
Section: Discussionmentioning
confidence: 99%